2015
DOI: 10.1007/978-3-319-18368-8_3
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Social Media Geographic Information (SMGI) in Spatial Planning

Abstract: This contribution reports on ongoing research carried on by the authors on the role of Social Media Geographic Information in spatial planning, design, and decision-making. Explicit and Implicit Volunteered Geographic Information (VGI) from social media platforms, namely Social Media Geographic Information (SMGI) resources, were used to explore novel methods and tools for analysis and knowledge construction. The results concern three main research streams carried on with the common feature of integrating socia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 19 publications
0
25
0
1
Order By: Relevance
“…Previous research has applied the DBSCAN algorithm to detect density clusters and extract activity centers for individuals from geo-tagged social media data [26,31]. Based on this research, we used DBSCAN to obtain each individual user's frequently visited areas.…”
Section: Extracting Activity Centersmentioning
confidence: 99%
“…Previous research has applied the DBSCAN algorithm to detect density clusters and extract activity centers for individuals from geo-tagged social media data [26,31]. Based on this research, we used DBSCAN to obtain each individual user's frequently visited areas.…”
Section: Extracting Activity Centersmentioning
confidence: 99%
“…(PIC!) (Campagna, Floris, Massa, Girsheva, & Ivanov, 2015) Nonetheless, there are disadvantages to using VGI in planning. Partly, this comes back to the issue of participant motivation, which in the context of planning, likely requires willingness to be coincident on two fronts: to contribute to the production of VGI, and to contribute to the planning process (Obermeyer, 2007).…”
Section: Volunteered Geographic Information In Urban Planningmentioning
confidence: 99%
“…Successful empirical studies of using geosocial media data for gauging public perceptions of disaster response, identifying events, and investigating human activities have also been documented [44][45][46]. In addition to the primary focus of mining spatial patterns, others suggested the need to further incorporate qualitative social media content [13]. Afzalan and Muller [47], for example, found that informative dialogues are developed within online groups regarding local green infrastructure planning issues.…”
Section: Use Of Geosocial Media In Local Governmentsmentioning
confidence: 99%
“…Gal-Tzur et al [11], similarly, suggested that useful information about transportation policy can be harvested from social media. The combination of qualitative and spatiotemporal analysis may, as suggested by Campagna [13], provide more insights into the geographies of public needs.…”
Section: Use Of Geosocial Media In Local Governmentsmentioning
confidence: 99%
See 1 more Smart Citation